2016
DOI: 10.1152/ajprenal.00129.2016
|View full text |Cite
|
Sign up to set email alerts
|

The enigma of continual plasma volume expansion in pregnancy: critical role of the renin-angiotensin-aldosterone system

Abstract: Pregnancy is characterized by avid renal sodium retention and plasma volume expansion in the presence of decreased blood pressure. Decreased maternal blood pressure is a consequence of reduced systemic vascular tone, which results from an increased production of vasodilators [nitric oxide (NO), prostaglandins, and relaxin] and decreased vascular responsiveness to the potent vasoconstrictor (angiotensin II). The kidneys participate in this vasodilatory response, resulting in marked increases in renal plasma flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 103 publications
4
57
0
3
Order By: Relevance
“…Figure 1 shows hemoglobin concentrations by trimester based on reports from Norway [19], Jamaica [20], and China [21]. [10,11], and it is hypothesized that the physiologic anemia of pregnancy serves the purpose of enhancing placental perfusion by reducing maternal blood viscosity and facilitating oxygen and nutrient delivery to the fetus by expanding the erythrocyte mass [12]. Beginning approximately the sixth week of pregnancy, the plasma volume increases disproportionately to the erythrocyte mass, reaching a maximum value at approximately 24 weeks' gestation.…”
Section: Physiologic Anemia Of Pregnancymentioning
confidence: 99%
“…Figure 1 shows hemoglobin concentrations by trimester based on reports from Norway [19], Jamaica [20], and China [21]. [10,11], and it is hypothesized that the physiologic anemia of pregnancy serves the purpose of enhancing placental perfusion by reducing maternal blood viscosity and facilitating oxygen and nutrient delivery to the fetus by expanding the erythrocyte mass [12]. Beginning approximately the sixth week of pregnancy, the plasma volume increases disproportionately to the erythrocyte mass, reaching a maximum value at approximately 24 weeks' gestation.…”
Section: Physiologic Anemia Of Pregnancymentioning
confidence: 99%
“…Again, what is known is that under non-pregnant conditions from rodent studies, ET-1 promotes sodium excretion via both ET receptors in females via NO signaling, whereas pregnancy is associated with increased GFR and renal blood flow via NO signaling but reduced sodium excretion due to attenuated NO signaling. Overall, this allows for plasma volume expansion of normal pregnancy [32], but the complete understanding of ET-1 involvement in this process is not yet fully elucidated. Although urinary levels of ET-1 are higher in pregnant versus non-pregnant women and increases as pregnancy progresses [33], it is unclear the relative levels of the different ET-1 cleavage products and their actions on vascular and renal function in proper blood pressure regulation during normal pregnancy.…”
Section: The Et System In Normal Pregnancymentioning
confidence: 99%
“…In this study, the level of serum NO was significantly decreased in the pregnant hypertensive rats, and as expected, RES supplementation significantly increased it to a level comparable to nonhypertensive pregnant control rats. Previous studies had demonstrated that NO is also a potent natriuretic agent, playing a major role in inhibiting epithelial sodium channel (ENaC) activity in the collecting duct [33], which hinted that the different antihypertensive mechanisms of RES might result in a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%